The use of microbial induced carbonate precipitation in healing cracks within reactive magnesia cement-based blends - Ruan, Shaoqin (2021)
This study investigated the feasibility of crack healing by means of microbial induced carbonate precipitation (MICP) in reactive magnesia cement (RMC)-based blends. Pre-cracked samples were subjected to four different healing conditions involving air, water and two different bacteria-urea concentrations. Resonance frequency measurements revealed the recovery of samples under different conditions. μ-CT, SEM-EDX, XRD and pH measurements were used to investigate the type and contents of healing products within the cracks. Different types of hydrated magnesium carbonates (HMCs) formed under each bacteria-urea solution due to differences in pH associated with bacteria-urea concentrations. While these phases first formed on top of the cracks, investigation of the crack depth revealed the presence of precipitates at inner sections, albeit at lower contents. The adopted MICP approach leading to the production of HMCs was an effective method for healing cracks in RMC-based samples, resulting in a high extent of healing in a short time period.